Off‐Equatorial Minima Effects on ULF Wave‐Ion Interaction in the Dayside Outer Magnetosphere. Issue 18 (22nd September 2021) - Li, Xing‐Yu; Liu, Zhi‐Yang; Zong, Qiu‐Gang; Zhou, Xu‐Zhi; Hao, Yi‐Xin; Pollock, Craig J.; Russell, Christopher T.; Lindqvist, Per‐Arne
Abstract: The ultra‐low frequency wave‐particle drift‐bounce resonance in the inner magnetosphere has been studied in detail, due to its important role in particle energization. However, it remains an open question how drift‐bounce resonance manifests in the dayside outer magnetosphere, where particles' orbits show bifurcations because of off‐equatorial magnetic field minima. In this study, we investigate this question, by analyzing Magnetospheric Multiscale observations of the January 20, 2017 event. A test‐particle simulation is conducted to help us understand the observations. The observed pitch angle‐time spectrograms show "pawtrack‐like" structures. We find there are more than two resonant pitch angles at fixed energy, since off‐equatorial minima change the relationship between the bounce (drift) frequency and pitch angle from unimodal function to trimodal function. These results reveal a new drift‐bounce acceleration mechanism in the dayside outer magnetosphere, which potentially affects the efficiency of particle energization during geomagnetic activities like geomagnetic storms. Plain Language Summary: The sun continuously ejects ionized gases called solar winds toward the Earth, affecting Earth's geomagnetic field. When the solar activity is strong, the geomagnetic field is severely disturbed, influencing the safety of power transmissions and space activities. This phenomenon is connected with particle acceleration in the geomagnetic field. The low frequency oscillation of geomagnetic field lines could efficiently transfer energy to charged particles in space, which plays an important role in particle acceleration. This study analyzes special observations which are different from the conventional pattern. A simulation is conducted to help interpret the observations. We find this low frequency magnetic field oscillation interacts with particles differently near the dayside boundary of the geomagnetic field, as the compression of the geomagnetic field by solar winds affects the motion of charged particles nearby. These results help us better understand the formation of geomagnetic activities. Key Points: The effects of off‐equatorial magnetic field minima on ultra‐low frequency wave‐ion interaction have been studied in this letter Off‐equatorial minima lead to more than two resonant pitch angles in drift‐bounce resonance The consequent pitch angle distribution shows "pawtrack‐like" structures